Analysis of the Impact of Load Imbalance on Neutral Current and Power Losses Caused by Neutral Current in Transformer 1, 30 MVA, 70/20 kV at Bungaran Substation - Azis, Abdul; Perawati; Yudi Irwansi; Muhammad Rizal (Asosiasi Riset Teknik Elektro dan Infomatika Indonesia, 2025)
Power transformers are crucial in the electrical distribution system, and their operational stability is significantly affected by load imbalance among phases. Load imbalance can lead to the flow of neutral current through the neutral conductor, causing additional power losses in the transformer. This study analyzes the impact of load imbalance on neutral current and power losses at Transformer 1 (30 MVA capacity, 70/20 kV) at the Bungaran Substation. Data such as phase current, neutral current, and power losses were measured at 12:00 and 21:00. At 12:00, the transformer’s full-load current was 839.17 A with a loading of 28.44% and a load imbalance of 0.74%, resulting in a neutral current of 4.36 A (1.83% of load current). The power loss due to neutral current was 12.64 W (4.36×10-5 %), and the loss due to neutral current flowing to the ground was 760 W (2.62×10-3 %). At 21:00, the full-load current decreased to 834.46 A, with a loading of 29.36% and a higher load imbalance of 1.36%. This caused a neutral current of 7.94 A (3.24%), with a power loss of 41.90 W (1.43×10-4 %) and a ground power loss of 2.52 W (8.60×10-3 %). The power losses were minimal compared to the transformer’s capacity, having little effect on system efficiency. However, maintaining load balance is essential for system efficiency and transformer longevity.